THE GROWTH OF MICROORGANISMS’ RESISTANCE TO ANTIMICROBIAL DRUGS DURING THE PANDEMIC: CHALLENGES AND STRATEGIES FOR OVERCOMING (Uzbekistan Open Conference, 2025)
The COVID-19 pandemic has significantly influenced the global increase of antimicrobial resistance (AMR). Excessive use of antibiotics, antiseptics, and disinfectants has led to the emergence of resistant strains of microorganisms. This article analyzes the main causes and mechanisms of resistance development and discusses modern strategies to overcome it, including rational antibiotic use, enhanced epidemiological surveillance, and the development of new therapeutic approaches.